Immunogenic cell death pathway polymorphisms for predicting oxaliplatin efficacy in metastatic colorectal cancer. Issue 2 (10th November 2020) - Arai, Hiroyuki; Xiao, Yi; Loupakis, Fotios; Kawanishi, Natsuko; Wang, Jingyuan; Battaglin, Francesca; Soni, Shivani; Zhang, Wu; Mancao, Christoph; Salhia, Bodour; Mumenthaler, Shannon M; Weisenberger, Daniel J; et al.
Abstract : Background: Immunogenic cell death (ICD) is a tumor cell death involving both innate and adaptive immune responses. Given published findings that oxaliplatin, but not irinotecan, drives ICD, we investigated whether single nucleotide polymorphisms (SNPs) in the ICD pathway are associated with the efficacy of oxaliplatin-based chemotherapy in metastatic colorectal cancer (mCRC). Methods: Two randomized clinical trials data were analyzed: discovery cohort, FOLFOX/bevacizumab arm (MAVERICC); validation cohort, FOLFOXIRI/bevacizumab arm (TRIBE); and two control cohorts, FOLFIRI/bevacizumab arms (both trials). Genomic DNA extracted from blood samples was genotyped. Ten SNPs in the ICD pathway were tested for associations with clinical outcomes. Results: In total, 648 patients were included. In the discovery cohort, three SNPs were significantly associated with clinical outcomes in univariate analysis: CALR rs1010222 with progression-free survival (G/G vs any A, HR=0.61, 95% CI 0.43–0.88), ANXA1 rs1050305 with overall survival (OS) (A/A vs any G, HR=1.87, 95% CI 1.04–3.35), and LRP1 rs1799986 with OS (C/C vs any T, HR=1.69, 95% CI 1.07–2.70). Multivariate analysis confirmed the trend, but statistical significance was not reached. In the validation cohort, ANXA1 rs1050305, and LRP1 rs1799986 were validated to have the significant associations with clinical outcome. No significant associations of these SNPs were observed in the two control cohorts. Treatment-by-SNP interaction test confirmed the predictive values. Conclusions: The predictive utility of ICD-related SNPs for the efficacy of oxaliplatin-based chemotherapy was demonstrated, warranting further validation studies to be translated into personalized treatment strategies using conventional cytotoxic agents in mCRC.